Heracles in early Greek epic - Tsaggalīs, Chrīstos K. (Mnemosyne. Supplementum. Monographs on Greek and Roman language and literature,, 2024)
Heracles in Early Greek Epic examines the protean nature of the greatest Greek hero, Heracles in Homeric and Hesiodic poetry, as well as in fragmentary epics such as Creophylus'Oichalias Halosis, Pisander's Heracleia, and Panyassis'Heracleia. Several contributors explore Heracles'associations with heroes in Near-Eastern literature and reflections in early epic about his involvement in the first sack of Troy, the tale of Hesione and the ketos, the war against the Meropes on Cos, and the sack of Oechalia. Other contributors study his role in other Archaic and Classical epics such as those written by Creophylus, Pisander, and Panyassis.